2015
DOI: 10.1136/bjophthalmol-2015-307292
|View full text |Cite
|
Sign up to set email alerts
|

The height of the posterior staphyloma and corneal hysteresis is associated with the scleral thickness at the staphyloma region in highly myopic normal-tension glaucoma eyes

Abstract: Subfoveal scleral thinning and non-uniform posterior staphyloma were closely related in highly myopic NTG eyes. Corneal hysteresis, corneal resistance factor and the nasal posterior staphyloma height were associated with the scleral thickness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Scleral staphylomas are a feature of highly myopic eyes. They have been described as outpouchings of a circumscribed region of the posterior sclera [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ]. Scleral staphylomas show a relatively abrupt scleral thinning at the staphyloma edge; a pronounced de-arrangement of scleral collagen fibrils; a marked, segmentally accentuated, choroidal thinning, most marked at the staphyloma border; and spatially correlated BM defects.…”
Section: Resultsmentioning
confidence: 99%
“…Scleral staphylomas are a feature of highly myopic eyes. They have been described as outpouchings of a circumscribed region of the posterior sclera [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ]. Scleral staphylomas show a relatively abrupt scleral thinning at the staphyloma edge; a pronounced de-arrangement of scleral collagen fibrils; a marked, segmentally accentuated, choroidal thinning, most marked at the staphyloma border; and spatially correlated BM defects.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies showed that a lower CH in patients with glaucoma was associated with increased deformation of the optic nerve surface during transient IOP elevation; but such correlation was not observed in normal controls. 32 Others have reported a correlation between a lower CH and a thinner scleral thickness in individuals with high myopia 33 and a correlation between a lower corneal deformation amplitude and a larger lamina cribrosa (LC) depth in primary open-angle glaucoma. 34 Our study identified a correlation between the cornea and the ONH's shear response in ostensibly normal donor eyes with no known ocular diseases, indicating a possible presence of a biomechanical relationship between the cornea and the posterior eye likely due to innate structural correspondence.…”
Section: Discussionmentioning
confidence: 99%